2012
DOI: 10.1063/1.4737792
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation and switching delay in stress-induced switching of multiferroic nanomagnets in the presence of thermal fluctuations

Abstract: Electrically controlled magnetization switching in a multiferroic heterostructure Appl. Phys. Lett. 97, 052502 (2010); 10.1063/1.3475417Effect of thermal fluctuations on switching field of deep submicron sized soft magnetic thin film Switching the magnetization of a shape-anisotropic 2-phase multiferroic nanomagnet with voltage-generated stress is known to dissipate very little energy (<1 aJ for a switching time of $0.5 ns) at 0 K temperature. Here, we show by solving the stochastic Landau-Lifshitz-Gilbert equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
140
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 37 publications
1
140
1
Order By: Relevance
“…The voltage generates strain in the piezoelectric, which is partially or completely transferred to the elliptical magnetostrictive soft layer,and rotates magnetization by the Villari effect [19][20][21][22][23][24][25] . It has been predicted theoretically that large angle (~90 o ) rotation in ~100 nm feature sized nanomagnets made of highly magnetostrictive materials (Terfenol-D, FeGa) will dissipate only ~1 aJ of energy to occur in ~1 ns [31][32][33] . Recent experiments have confirmed that the energy dissipated to switch a nanomagnet in this fashion will be on the order of 1 aJ in properly scaled structures.…”
mentioning
confidence: 99%
“…The voltage generates strain in the piezoelectric, which is partially or completely transferred to the elliptical magnetostrictive soft layer,and rotates magnetization by the Villari effect [19][20][21][22][23][24][25] . It has been predicted theoretically that large angle (~90 o ) rotation in ~100 nm feature sized nanomagnets made of highly magnetostrictive materials (Terfenol-D, FeGa) will dissipate only ~1 aJ of energy to occur in ~1 ns [31][32][33] . Recent experiments have confirmed that the energy dissipated to switch a nanomagnet in this fashion will be on the order of 1 aJ in properly scaled structures.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21] It has been widely investigated in various piezoelectric/ferromagnetic bilayer thin films [22][23][24][25][26] or nano-structures. [27][28][29][30] There are also several theoretical predications [31][32][33] that such a method will dissipate only a few atto-Joules (aJ) of energy to write data. This establishes the promise of using strain to control the resistance of an MTJ for ultra-energy-efficient memory applications.…”
mentioning
confidence: 99%
“…The thermal field is described as a Gaussian random process 21 including a Gaussian distribution with zero mean and unit variance. 22 The random numbers g(τ ) that are used are then generated through the use of the Box-Müller algorithm 23 and vary between ±1 at each time step. The thermally induced field h therm (where the H therm is normalization by N x ), is introduced into the Landau-LifshitzGilbert equations alongside the applied magnetic field h app,j , so that h j = h app,j + h therm , with j = x, y, or z.…”
Section: Comparison Of the Quasistatic And Dynamical Resultsmentioning
confidence: 99%